Water Defluoridation by Adsorption Using Aluminium Modified Chicken Feathers - Nasiebanda , Roselyne; Wambu , E. Wamalwa; Lusweti , Kituyi (African Journal of Education,Science and Technology (AJEST), 2021)
Sufficient fluoride (F-) ingestion through food, soil and water is necessary for the development of healthy bones and teeth while excess of it results in dental, skeletal and soft tissue damage. To protect people from fluorosis, it is therefore, important for the F- to be removed from water. In the current study, F- removal by adsorption method from aqueous solutions using chicken feathers modified by Al3+ was studied using batch experiments. The feathers collected from Kitale slaughter house were ground, weighed, treated and tested for defluoridation. The adsorbent was characterized by FTIR and SEM methods. The effect of F- levels, adsorbent dosage, contact time, temperature, and pH and agitation rate were also investigated. The results showed that fluoride adsorption increased from around 48.5% to 88.9% with adsorbent mass increase from 0.1 g to 0.8 g. The percentage F- uptake by the adsorbent then increased to nearly 94.6% when the adsorbent mass was further increased to 1.6 g, but a higher increase in mass resulted in a constant adsorption percentage. Additionally, the percentage removal of F- increased from 71% at a period of 1 minute to a highest % of 95 after 60 minutes. Furthermore, the % adsorption increased from 66% with agitation rate of 35 rpm to an optimum agitation rate of 300 rpm with % adsorption of 90. Fluoride adsorption increased from 82% to 90% with rise in solution pH of 1 to 5 but dropped beyond pH 7. It was further observed that % adsorption increased from 87-94% between a temperature range of 293-313 K, and decreased between a higher temperature range of 313-353 K. The percentage adsorption removal increased from 76-99 % within the range of initial fluoride concentration of 2.5-40 mg/L, and there after decreased. However, the F- adsorption data correlated to the Freundlich and Langmuir models and could be classified as C-Type according to Giles classification of isotherms. The pseudo-first and pseudo-second order kinetic models and the Weber and Morris intra particle diffusion model equation were applied onto the adsorbent. The adsorbent could thus be used as an inexpensive adsorbent for the removal of F- ions from aqueous streams.